2016
DOI: 10.1097/hjh.0000000000000875
|View full text |Cite
|
Sign up to set email alerts
|

Tripartite motif-containing 55 identified as functional candidate for spontaneous cardiac hypertrophy in the rat locus cardiac mass 22

Abstract: Our study suggests that the Trim55 gene, located in Cm22, is a novel candidate gene for polygenic LV hypertrophy independent of blood pressure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…DNA sequence variants in HHR were identified according to methods detailed previously (30). Briefly, we sequenced the whole genome of 1 male 13-wk-old NHR and 1 age-matched HHR.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…DNA sequence variants in HHR were identified according to methods detailed previously (30). Briefly, we sequenced the whole genome of 1 male 13-wk-old NHR and 1 age-matched HHR.…”
Section: Methodsmentioning
confidence: 99%
“…Variants were analyzed according to Genome Analysis Toolkit best practices (35), and functional annotation was performed using SnpEff software (4). Results were stored in a database developed in house, and then we identified unique single nucleotide polymorphisms (SNPs) and insertions/deletions (InDels) in the NHR and HHR (30). Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, the results of a randomized study indicated that MuRF1 expression decreased in the skeletal muscle of patients with chronic heart failure after they completed exercise training [69]. In a spontaneous cardiac hypertrophy mouse model, Prestes et al [70] found that MuRF2 is a novel candidate gene for cardiac hypertrophy. The functions of MuRF2 and MuRF3 also overlap during binding to microtubules, and both are involved in sarcomere formation.…”
Section: Muscle Ring Finger Protein Familymentioning
confidence: 99%
“…Tripartite motif-containing protein 44 (Trim44), which was first cloned in 2001 by Effrossini Boutou et al (2001) , has been identified as a member of the TRIM protein family. TRIM family proteins, most of which have E3 ubiquitin ligase activities, are involved in a variety of cellular processes, such as apoptosis, development, growth and signal transduction ( Di Fiore et al, 2003 ; Hershko and Ciechanover, 1998 ; Yang et al, 2020 ; Chen et al, 2016 , 2017 ; Prestes et al, 2016 ; Heliste et al, 2020 ; Zungu et al, 2011 ; Salazar-Mendiguchía et al, 2020 ). TRIM family proteins are also involved in multiple diseases, including those affecting innate immunity and neurodevelopment, cardiovascular diseases and carcinogenesis ( Yang et al, 2013 ; Leong et al, 2002 ; Hatakeyama, 2011 ; Järvinen et al, 2008 ; Urano et al, 2009 ; Boutou et al, 2001 ).…”
Section: Introductionmentioning
confidence: 99%